Analisis Pengaruh Implementasi Kampus Merdeka Dan Persepsi Terhadap Minat Mengikuti Program Merdeka Belajar Kampus Merdeka Mahasiswa Fakultas Ilmu Sosial Dan Ekonomi - Sartika Komala Sari; Baiq Yuliana Rizkiwati; Baiq Dian Septiana; Sulastri Maherlin; Tania Novita (Universitas Hamzanwadi, 2024)
This research is a quantitative descriptive study. Quantitative research is a form of research that uses numerical data collection and analytical techniques to test hypotheses, draw conclusions, and understand the relationships between the variables studied. The purpose of this study was to analyze the implementation of the Independent Campus and perceptions of interest in participating in the MBKM program. The population of this study were active students at the Faculty of Social Sciences and Economics in the 6th semester. The research sample size was 130 students. The technique used in the research sampling was a questionnaire. A questionnaire is a data collection technique carried out by providing a set of written questions or statements to respondents to answer. The data analysis technique used in this study was multiple linear regression analysis because it has two independent variables and one dependent variable. The findings of this study indicate that; First, the implementation of the independent campus influences the interest in participating in the MBKM program, Second, student perception influences the interest in participating in the MBKM program and third, the implementation of the Independent Campus and student perception simultaneously influence the interest in participating in the MBKM program with a determination coefficient of 0.398 or 39.8% of student interest is influenced by the implementation of the independent campus and student perceptions about MBKM, the remaining 60.2% is influenced by other factors not included in the model in this study.